Validation of Water Radiolysis Models Against Experimental Data in Support of the Prediction of the Radiation-Induced Corrosion of Copper-Coated Used Fuel Containers - Scott Briggs; Mehran Behazin; Fraser King (Corrosion and Materials Degradation, 2025)
Copper has been proposed as a container material for the disposal of used nuclear fuel in a number of countries worldwide. The container materials will be subject to various corrosion processes in a deep geological repository, including radiation-induced corrosion (RIC) resulting from the γ-irradiation of the near-field environment. A comprehensive model is being developed to predict the extent of RIC by coupling a radiolysis model to the interfacial electrochemical reactions on the container surface. An important component of the overall model is a radiolysis model to predict the time-dependent concentration of oxidizing and reducing radiolysis products. As a first step in the model development, various radiolysis models have been validated against experimental measurements of the concentrations of dissolved and gaseous radiolysis products. Experimental data are available for pure H2O- and Cl−-containing solutions, with and without a gas headspace. The results from these experiments have been compared with predictions from corresponding radiolysis models, including the effects of the partitioning of gaseous species (O2 and H2) at the gas–solution interface. Different reaction schemes for the Cl− radiolysis models are also compared. The validated radiolysis model will then be coupled with interfacial reactions on the copper surface and additional processes related to the presence of bentonite clay in Steps 2 and 3 of the overall model, respectively.